Household human development index and measurement: a study of Muslims in Kashmir - Naik, Asif; Selvarajan, E. (International Journal of Health, 2016)
Sustainable development of Muslims in India is one of the major challenges before the planners and policy makers particularly in the State of Jammu and Kashmir at a phase when India has registered growth in all spheres of life. Yet, the major question that still remains unanswered is as how far have the Muslims of Jammu and Kashmir benefited from the fruits of development (Naik 2013, 143-49). The answer particularly depends upon the ways through which development is conceived and measured. The development strategies must aim at the integration of the people of the region of Kashmir with rest of the country (Naik 2015, 614-616). The present paper attempts to measure human development of the Muslim households of Kashmir regions. Further, it attempts to examine the interrelationship among various indicators of HDI and will depict the extent of achievements of the surveyed villages ranking them as per their human development index adopted. It also suggests policy measures to improve HDI in the study region.